IBD-mediated oxidative cyclization of pyrimidinylhydrazones and concurrent Dimroth rearrangement: Synthesis of [1,2,4]triazolo[1,5-c]pyrimidine derivatives - Tang, Caifei; Li, Zhiming; Wang, Quanrui (Beilstein Journal of Organic Chemistry, 2013)
Oxidative cyclization of 6-chloro-4-pyrimidinylhydrazones 4 with iodobenzene diacetate (IBD) in dichloromethane gives rise to [1,2,4]triazolo[4,3-c]pyrimidine derivatives 5a–o. These incipient products undergo feasible Dimroth rearrangement to furnish the isolated [1,2,4]triazolo[1,5-c]pyrimidines 6a–o in moderate to high yields.
Keywords: cyclization; hydrazones; hypervalent iodine; oxidation; rearrangement; [1,2,4]triazolo[1,5-c]pyrimidines